RNAi construct of a cytochrome P450 gene CYP82D109 blocks an early step in the biosynthesis of hemigossypolone and gossypol in transgenic cotton plants. (July 2015) - Wagner, Tanya A.; Liu, Jinggao; Puckhaber, Lorraine S.; Bell, Alois A.; Williams, Howard; Stipanovic, Robert D.
Graphical abstract: RNAi knock-down of a gossypol pathway cytochrome P450 hydroxylase gene CYP82D109 cloned from cotton resulted in the blockage of gossypol and heliocides biosynthesis. It also enhanced the pathogen induced lacinilene C pathway in cotton. Highlights: A P450 gene ( CYP82D109 ) involved in biosynthesis of gossypol in cotton is cloned. Plants with RNAi have reduced levels of terpenoid aldehydes. Plants with RNAi accumulate the volatile terpene, δ-cadinen-2-one. The lacinilene C and gossypol pathways are linked in RNAi plants. Lacinilene C pathway induction by fungal challenge is greater in RNAi plant leaves. Abstract: Naturally occurring terpenoid aldehydes from cotton, such as hemigossypol, gossypol, hemigossypolone, and the heliocides, are important components of disease and herbivory resistance in cotton. These terpenoids are predominantly found in the glands. Differential screening identified a cytochrome P450 cDNA clone ( CYP82D109 ) from a Gossypium hirsutum cultivar that hybridized to mRNA from glanded cotton but not glandless cotton. Both the D genome cotton Gossypium raimondii and A genome cotton Gossypium arboreum possessed three additional paralogs of the gene. G. hirsutum was transformed with a RNAi construct specific to this gene family and eight transgenic plants were generated stemming from at least five independent transformation events. HPLC analysis showed that RNAi plants, when compared to wild-type Coker 312 (WT) plants, had a 90% reduction in hemigossypolone and heliocides levels, and a 70% reduction in gossypol levels in the terminal leaves, respectively. Analysis of volatile terpenes by GC–MS established presence of an additional terpene (MW: 218) from the RNAi leaf extracts. The 1 H and 13 C NMR spectroscopic analyses showed this compound was δ-cadinen-2-one. Double bond rearrangement of this compound gives 7-hydroxycalamenene, a lacinilene C pathway intermediate. δ-Cadinen-2-one could be derived from δ-cadinene via a yet to be identified intermediate, δ-cadinen-2-ol. The RNAi construct of CYP82D109 blocks the synthesis of desoxyhemigossypol and increases the induction of lacinilene C pathway, showing that these pathways are interconnected. Lacinilene C precursors are not constitutively expressed in cotton leaves, and blocking the gossypol pathway by the RNAi construct resulted in a greater induction of the lacinilene C pathway compounds when challenged by pathogens.